2000
DOI: 10.1002/(sici)1526-4998(200001)56:1<94::aid-ps105>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and acaricidal activity of 4‐pyrimidinyloxy‐ and 4‐pyrimidinylaminoethylphenyl dioxolanes and oxime ethers

Abstract: Novel types of mitochondrial respiration inhibitors at complex I, with emphasis on acaricidal activity, have been designed and prepared. The synthetic approach to these 4-pyrimidinylphenyl ethyl ethers and amines with a speci®c ketal or oxime function in the phenyl side chain is outlined. Bioassays demonstrate their high potential against important spider mites, like Tetranychus urticae and Panonychus ulmi. Structure±activity relationship studies and several biological parameters are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The inhibitors with fluoroalkyl or fluoroacyl substituents are much more potent than the alkyl or acyl derivatives. A variety of the reports regarding synthetic studies of quinazolinone derivatives have been presented because of the chemical and biological interests to quinazolines . Quinazoline compounds are widely used in agrochemicals as plant virucides , antifungal agents , and herbicides .…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitors with fluoroalkyl or fluoroacyl substituents are much more potent than the alkyl or acyl derivatives. A variety of the reports regarding synthetic studies of quinazolinone derivatives have been presented because of the chemical and biological interests to quinazolines . Quinazoline compounds are widely used in agrochemicals as plant virucides , antifungal agents , and herbicides .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, quinazoline compounds have been found to possess biological activities in medicine and pesticide [1][2][3][4] . As part of our ongoing research on heterocyclic compounds that may serve as leads for designing novel antifungal agents, we are particularly interested in 4-substituted thioquinazolines [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…1). The structures of the 4-thioquinazoline compounds were characterized by elemental analyses as well as IR, 1 H and 13 C NMR spectroscopies. Preliminary biological tests showed that some of the compounds exhibited good antifungal activities.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of the reports regarding synthetic studies of quinazolinone derivatives have been presented due to the chemical and biological interests to the quinazoline [1,2]. Quinazoline compounds are widely used in agrochemicals as plant virucides [3], antifungal agents [4] and herbicides [5].…”
Section: Introductionmentioning
confidence: 99%